Lincoln and the military - Marszalek, John F., 1939- (Concise Lincoln library., 2014)
When Abraham Lincoln was elected president of the United States in 1860, he came into office with practically no experience in military strategy and tactics. Consequently, at the start of the Civil War, he depended on leading military men to teach him how to manage warfare. As the war continued and Lincoln matured as a military leader, however, he no longer relied on the advice of others and became the major military mind of the war. In this brief overview of Lincoln's military actions and relationships during the war, John F. Marszalek traces the sixteenth president's evolution from a nonmi.